2012
DOI: 10.1134/s102144371201013x
|View full text |Cite
|
Sign up to set email alerts
|

Change in antioxidant responses against oxidative damage in black chickpea following cold acclimation

Abstract: Cold stress is an important factor affecting chickpea (Cicer arietinum L.) plants in winter and early spring. We evaluated the effects of cold stress by measuring lipid peroxidation, membrane permeability, and some enzyme activities involved in the ROS scavenging system under acclimation and non acclimation con ditions in black chickpea Kaka, a popular genotype planted, and accession 4322, as a landrace genotype. Under non acclimation conditions, the genotype 4322 prevented the H 2 O 2 accumulation more effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…The enzyme CAT removes H 2 O 2 by breaking it down to form H 2 O and oxygen, and oxidizes H donors with the consumption of peroxide. We have demonstrated that CAT activity increased in all the resistant, one susceptible, and one semiresistant chickpea cultivar / advanced line under cold stress, which is a similar finding to some other researchers [25][26][27]. Cicer arietinum 'Saral' , the most novel genotype studied, appropriately reacted to MS and showed high CAT activity, but with intensification of cold stress, the activity of this enzyme decreased.…”
Section: Discussionsupporting
confidence: 89%
“…The enzyme CAT removes H 2 O 2 by breaking it down to form H 2 O and oxygen, and oxidizes H donors with the consumption of peroxide. We have demonstrated that CAT activity increased in all the resistant, one susceptible, and one semiresistant chickpea cultivar / advanced line under cold stress, which is a similar finding to some other researchers [25][26][27]. Cicer arietinum 'Saral' , the most novel genotype studied, appropriately reacted to MS and showed high CAT activity, but with intensification of cold stress, the activity of this enzyme decreased.…”
Section: Discussionsupporting
confidence: 89%
“…There was a significantly higher ion leakage, higher percentage of water loss from the excised leaf, and relatively low weight of the saturated leaf of the VIGS plants compared to their wild types under drought and salt stress conditions. Reduction in SLW, increased ion leakage, and percentage water loss from the excised leaf are indications that the VIGS plants suffered intensive oxidative stress, and thus lost the ability to tolerate the effects of drought and salinity stress [71]. Moreover, oxidant and antioxidant enzyme assays showed that the VIGS plants registered higher levels of oxidant enzymes and a significant reduction of the antioxidant enzymes under salt and drought stress conditions compared to their wild types.…”
Section: Discussionmentioning
confidence: 99%
“…There is a close relation between ROS formation and oxidative stressinduced damages to cell membranes (Nazari et al, 2012). ROS degrades polyunsaturated membrane lipids, forming MDA.…”
Section: Foliar Application Of Tio 2 Np Under Water-deficit Stressmentioning
confidence: 99%